Penerapan Konsep Natural di Interior Ruang Spa Pada Bangunan Pusat Kebugaran dan Spa di Banda Aceh - Nuratul Hikmah (Universitas Syiah Kuala, 2018)
Working under continuous work pressure and competition makes people today very prone to stress. Thereore, keeping oneself in very good health condition and avoiding stress are amongst lifestyle of people today, especially those living in the urban area. In eliminating fatigue and re-fit of course this urban community will find entertainment places that can support the health of the body and make the mind relaxed again. This will be a consideration in designing a fitness center and spa using a natural concept approach. The applied natural concept will bring nature inside a building in which gives relaxing atmosphere. Materials that will also have to be considered well in order to convey the concept of nature are wood, bamboo, natural stone, as well as other natural materials. The Spa and Fitness Center is located in the city center of Banda Aceh, so users do not have to travel all the way to the mountains or countryside to seek a natural setting as this natural atmosphere will be present in the middle of the city in the gym and spa building that will be designed.